Axial length and cone density as assessed with adaptive optics in myopia - Dabir, Supriya; Mangalesh, Shwetha; Schouten, Jan; Berendschot, Tos; Kurian, Mathew; Kumar, Anupama; Yadav, Naresh; Shetty, Rohit (Indian journal of ophthalmology, 2015)
Aim: To assess the variations in cone mosaic in myopia and its correlation with axial length (AL). Subjects and Methods: Twenty-five healthy myopic volunteers underwent assessment of photoreceptors using adaptive optics retinal camera at 2° and 3° from the foveal center in four quadrants superior, inferior, temporal and nasal. Data was analyzed using SPSS version 17 (IBM). Multivariable regression analysis was conducted to study the relation between cone density and AL, quadrant around the fovea and eccentricity from the fovea. Results: The mean cone density was significantly lower as the eccentricity increased from 2° from the fovea to 3° (18,560 ± 5455-16,404 ± 4494/mm 2 respectively). There was also a statistically significant difference between four quadrants around the fovea. The correlation of cone density and spacing with AL showed that there was a significant inverse relation of AL with the cone density. Conclusion: In myopic patients with good visual acuity cone density around the fovea depends on the quadrant, distance from the fovea as well as the AL. The strength of the relation of AL with cone density depends on the quadrant and distance.